Single-agent ibrutinib in RESONATE-2™ and RESONATE™ versus treatments in the real-world PHEDRA databases for patients with chronic lymphocytic leukemia - Salles, Gilles; Bachy, Emmanuel; Smolej, Lukas; Simkovic, Martin; Baseggio, Lucile; Panovska, Anna; Besson, Hervé; Healy, Nollaig; Garside, Jamie; Iraqi, Wafae; Diels, Joris; Pick-Lauer, Corinna; et al. (Annals of hematology, 2019)
After analyzing treatment patterns in chronic lymphocytic leukemia (CLL) (objective 1), we investigated the relative effectiveness of ibrutinib versus other commonly used treatments (objective 2) in patients with treatment-naïve and relapsed/refractory CLL, comparing patient-level data from two randomized registration trials with two real-world databases. Hazard ratios (HR) and 95% confidence intervals (CIs) were estimated using a multivariate Cox proportional hazards model, adjusted for differences in baseline characteristics. Rituximab-containing regimens were often prescribed in clinical practice. The most frequently prescribed regimens were fludarabine + cyclophosphamide + rituximab (FCR, 29.3%), bendamustine + rituximab (BR, 17.7%), and other rituximab-containing regimens (22.0%) in the treatment-naïve setting (n = 604), other non-FCR/BR rituximab-containing regimens (38.7%) and non-rituximab-containing regimens (28.5%) in the relapsed/refractory setting (n = 945). Adjusted HRs (95% CI) for progression-free survival (PFS) and overall survival (OS), respectively, with ibrutinib versus real-world regimens were 0.23 (0.14-0.37; p < 0.0001) and 0.40 (0.22-0.76; p = 0.0048) in the treatment-naïve setting, and 0.21 (0.16-0.27; p < 0.0001) and 0.29 (0.21-0.41; p < 0.0001) in the relapsed/refractory setting. When comparing real-world use of ibrutinib (n = 53) versus other real-world regimens in relapsed/refractory CLL (objective 3), adjusted HRs (95% CI) were 0.37 (0.22-0.63; p = 0.0003) for PFS and 0.53 (0.27-1.03; p < 0.0624) for OS. This adjusted analysis, based on nonrandomized patient data, suggests ibrutinib to be more effective than other commonly used regimens for CLL.
Keywords: Bendamustine Hydrochloride; Ibrutinib; dospělí; Cyclophosphamide; Female; pyrimidiny; Adenine; Adult; ženské pohlaví; Vidarabine; Leukemia, Lymphocytic, Chronic, B-Cell; přežití bez známek nemoci; bendamustin hydrochlorid; Pyrazoles; Chronic lymphocytic leukemia; lidé; pyrazoly; Rituximab; databáze faktografické; Aged, 80 and over; míra přežití; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Middle Aged; Real-world evidence; adenin; Male; Aged; Piperidines; rituximab; Randomized controlled trial; Survival Rate; Databases, Factual; vidarabin; Disease-Free Survival; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Overall survival; Progression-free survival; cyklofosfamid; piperidiny; chronická lymfatická leukemie; Pyrimidines; Humans